Hubungan Pengetahuan Ibu Tentang Infeksi Kecacingan dengan Status Gizi Balita di Wilayah Kerja Puskesmas Gambut Kabupaten Banjar Tahun 2015 - Rahmi Noerdiana Hidayati; Sugeng Riyanto; Alfia Rahma; STIKES Husada Borneo; Puskesmas Gambut; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2015)
Nutrition is one determinant of the quality of human resources. The food is given daily nutrition should contain as needed, so that support optimal growth and can prevent deficiency diseases, prevent poisoning, and also help prevent diseases that can interfere with the survival of children. The main factor cause of malnutrition is unbalanced food intake and infectious diseases. Both of these factors are closely related to lack of food availability at household level, poor parenting and inadequate health care. This study aims to determine the relationship mother Knowledge About Helminthiases Against Infection Toddler Nutritional Status in Puskesmas Gambut Regency Banjar in 2015. This study used analytic survey with cross sectional study with sampling techniques performed Accidental Sampling. This study was conducted on 47 respondents mothers and children aged ≥ 2 years - ≤ 5 years. Results of statistical analysis using SPSS spaerman test on a computer p value = 0,000, this value is smaller than α = 0,05. Which is interpreted H0 is rejected, it means that there is a correlation mother knowledge about worm infection with nutritional status of children.